Cultural control methods improve management of leafhopper vector of X-disease - Adrian T. Marshall; Tawnee D. Melton; Garrett Bishop; Abigail E. Clarke; Cesar A. Reyes-Corral; Katlyn A. Catron; Louis B. Nottingham; Tobin D. Northfield (Crop Protection, 2024)

Effects of a field-sprayed antibiotic on bee foraging behavior and pollination in pear orchards - Laura Avila; Christopher McCullough; Annie Schiffer; JoMari Moreno; Neha Ganjur; Zachary Ofenloch; Tianna DuPont; Louis Nottingham; Nicole M. Gerardo; Berry J. Brosi (Agriculture, Ecosystems & Environment, 2024)

Characterizing Substrate-Borne Vibrational Mating Signals Produced by Pear Psylla, Cacopsylla pyricola (Hemiptera: Psyllidae) - Dowen Mae I. Jocson; Mark T. Gonzales; David R. Horton; Louis B. Nottingham; Elizabeth H. Beers; Liesl C. Oeller; David W. Crowder (Journal of Insect Behavior, 2023)
Tactics that manipulate insect behavior are a component of many pest management strategies. Pheromone-based mating disruption is one such tactic widely used in agricultural systems, but few studies have assessed disrupting other mate communication mechanisms, such as acoustic signals. The most destructive pear pest in the Pacific Northwest USA, pear psylla ( Cacopsylla pyricola ) is believed to use acoustic signals to find mates, making it a candidate for this type of disruption. This species has two adult morphs, overwintering adults (winterforms) that emerge in the spring and subsequent generations (summerforms). Our study characterized the mating signals for both sexes and morphs of pear psylla, and assessed whether temperature and previous exposure to adult conspecifics altered signals and likelihood of signaling. While there are descriptions for acoustic signals of other psyllid species, this study provides the first evidence that C. pyricola communicates acoustically. The two sexes communicate via duetting; males signal to attract a female and the female signals back if she is receptive for mating. We showed that both morphotypes’ male signals contain a group of chirps followed by a trill, while females respond with chirps . Male signal trills differed significantly in frequency (Hz) between winterform and summerform psylla. The signal frequency among morphs also had a positive linear relationship with temperature, suggesting that dissimilarity in signals among morphs had some relationship to temperature. Males were more likely to signal when they had previous exposure to females compared to males without exposure to females. Our results provide new information on how pear psylla communicate acoustically for mating, advancing the potential to develop mating disruption strategies for integrated pest management (IPM).